2016
DOI: 10.1080/2162402x.2016.1219828
|View full text |Cite
|
Sign up to set email alerts
|

Peritumoral stromal neutrophils are essential for c-Met-elicited metastasis in human hepatocellular carcinoma

Abstract: Inflammation is a component of tumor progression mechanisms. Neutrophils are a common inflammatory infiltrate in many tumors, but their regulation and functions in neoplasia are not understood. Here, we showed, in detailed studies of c-Met molecule in 225 untreated patients with hepatocellular carcinoma (HCC), that high infiltration of neutrophils in HCC tissues determined malignant cell c-Met-associated clinical outcome of patients. High infiltration of neutrophils in HCCs determined malignant cell c-Metassoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
51
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(51 citation statements)
references
References 47 publications
0
51
0
Order By: Relevance
“…In mouse breast cancer, the IL-17-producing γδ T cells induced neutrophils to expand and acquire an N2 phenotype, suppressing CD8 + T cell activation and promoting lung metastasis (9). In human hepatocellular carcinoma (HCC), neutrophils accumulated at the invading tumor edge and represented the major source of HGF, which promoted HCC metastasis via interaction with c-Met in HCC cells (10). In human germinal center B-cell lymphoma, neutrophils could trigger the activation of the nuclear factor-κB (NF-κB) pathway in stromal cells, which…”
Section: Introductionmentioning
confidence: 99%
“…In mouse breast cancer, the IL-17-producing γδ T cells induced neutrophils to expand and acquire an N2 phenotype, suppressing CD8 + T cell activation and promoting lung metastasis (9). In human hepatocellular carcinoma (HCC), neutrophils accumulated at the invading tumor edge and represented the major source of HGF, which promoted HCC metastasis via interaction with c-Met in HCC cells (10). In human germinal center B-cell lymphoma, neutrophils could trigger the activation of the nuclear factor-κB (NF-κB) pathway in stromal cells, which…”
Section: Introductionmentioning
confidence: 99%
“…Conditioned media from HGF producing TANs promoted hepatoma cell migration, whereas the media from blood derived neutrophils, which produce less HGF did not. In addition, treatment of TANs with c-MET inhibitors reduced TAN associated hepatoma cell migration (51).…”
Section: Leukocytes and C-met Expressionmentioning
confidence: 99%
“…c-MET silencing in neutrophils resulted in increased tumor growth in mice, demonstrating c-MET positive neutrophils have anti-tumor properties (48). Furthermore, in-vitro experiments showed c-MET knock out neutrophils have reduced nitric oxide-mediated cytotoxicity against neoplastic cells, whereas c-MET positive, HGF-stimulated neutrophils demonstrated increased nitric oxide The role of TANs in c-MET associated patient outcomes has been investigated in treatment naive patients with hepatocellular carcinoma (HCC) (51). Although, tumor cell c-MET expression when considered alone was not predictive of outcome, MET expression by HCC cells was inversely associated with overall survival and disease free progression times in the subgroup of patients within this cohort with large numbers of neutrophils at the invading tumor margins (51) Further in-vitro work by this group, determined that exposing neutrophils to culture supernatants from HCC cell lines or primary HCC cells increased production of HGF by neutrophils.…”
Section: Leukocytes and C-met Expressionmentioning
confidence: 99%
“…Because 59% of MET-overexpressing breast cancer expresses HGF in stromal cells (31), it is likely that MET signal in cancer cells is activated in a paracrine manner in a certain number of breast cancers. Several studies have shown that fibroblasts or neutrophils in squamous cell carcinoma or hepatocellular carcinoma secrete HGF and promote invasion of cancer cells (32)(33)(34), which indicate these stromal cells as a source of HGF in the tumor microenvironment. However, in our models of breast cancer pulmonary metastasis, MAMs rather than neutrophils expressed high HGF and fibroblasts are rarely found in these metastatic tumors.…”
Section: Discussionmentioning
confidence: 99%